2018
DOI: 10.1634/theoncologist.2017-0535
|View full text |Cite
|
Sign up to set email alerts
|

Luminal A Breast Cancer and Molecular Assays: A Review

Abstract: Immunohistochemical markers have traditionally guided treatment decisions in breast cancer. However, advances in gene-expression profiling and availability of gene-based assays have launched these newer tests into everyday clinical practice. Luminal A-subtype tumors are a unique subset that may have favorable tumor biology. Properly defining this tumor subtype is important and may identify a subset of patients for whom endocrine therapy alone is sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 69 publications
1
123
0
9
Order By: Relevance
“…According to the last update of St. Gallen in 2013, the immunohistochemical profile of this subtype was defined as: ER+ (≥ 1%), high expression of PR (≥ 20%), HER2-(≤ 10%), and low levels of Ki-67 (< 14%) 42 . In addition, these tumors have characteristics of luminal epithelial cells of the breast, such as the high expression of cytokeratin's 7/8/18/19 43 . They include a wide range of low histological grade variants, such as IDC-NST, tubular, cribriform, mucinous, and classic ILC 6,43 .…”
Section: Luminal Amentioning
confidence: 99%
See 1 more Smart Citation
“…According to the last update of St. Gallen in 2013, the immunohistochemical profile of this subtype was defined as: ER+ (≥ 1%), high expression of PR (≥ 20%), HER2-(≤ 10%), and low levels of Ki-67 (< 14%) 42 . In addition, these tumors have characteristics of luminal epithelial cells of the breast, such as the high expression of cytokeratin's 7/8/18/19 43 . They include a wide range of low histological grade variants, such as IDC-NST, tubular, cribriform, mucinous, and classic ILC 6,43 .…”
Section: Luminal Amentioning
confidence: 99%
“…In addition, these tumors have characteristics of luminal epithelial cells of the breast, such as the high expression of cytokeratin's 7/8/18/19 43 . They include a wide range of low histological grade variants, such as IDC-NST, tubular, cribriform, mucinous, and classic ILC 6,43 . This subtype has been associated with a highly favorable prognosis, with a more indolent clinical course, and generally shows less lymph node involvement 44 .…”
Section: Luminal Amentioning
confidence: 99%
“… 6 Each subtype might have different treatment strategies, and the predictive factors may not be the same. For example, the best treatment regimen for breast cancer with luminal A subtype, which is clinically acceptable, is endocrine therapy alone without chemotherapy, 17 whereas for luminal B subtype, the optimal combination of chemotherapy and endocrine therapy is necessary. Recently, the PAMELA study showed that breast cancer patients with the HER2+ subtype are more likely to benefit from the dual HER2 blockade treatment.…”
Section: Pathological Featuresmentioning
confidence: 99%
“…Moreover, tumor molecular subtypes enable to inform clinical outcomes and treatments. For example, treatment options can be made based on either Her2+, luminal or basal subtypes of breast cancer ( 1, 2, 3, 4 ). However, the enormous complexity of cancer subtypes, tumor microenvironment, subclones, and somatic genomic alteration landscapes has been reported.…”
Section: Introductionmentioning
confidence: 99%